2011
DOI: 10.1038/onc.2011.195
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2 is a direct transcriptional target of hedgehog signaling and involved in stroma-induced drug tolerance in diffuse large B-cell lymphoma

Abstract: Successful treatment of diffuse large B-cell lymphoma (DLBCL) is frequently hindered by development of resistance to conventional chemotherapy resulting in disease relapse and high mortality. High expression of anti-apoptotic and/or drug transporter proteins induced by oncogenic signaling pathways has been implicated in the development of chemoresistance in cancer. Previously, our studies showed high expression of ATP-binding cassette drug transporter ABCG2 in DLBCL correlated inversely with disease-free and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
115
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(133 citation statements)
references
References 60 publications
14
115
3
1
Order By: Relevance
“…This activation of GLI1 is not due to amplifications of GLI1 (22) or mutations of Hhrelated genes (23,24). Our data support that the Hh pathway in DLBCL is aberrantly activated as its activation is in part mediated by external Hh ligands (autocrine and paracrine Hh signaling loops) (5,16) but also intrinsically by cross-talks with other oncogenic pathways (22).…”
supporting
confidence: 72%
“…This activation of GLI1 is not due to amplifications of GLI1 (22) or mutations of Hhrelated genes (23,24). Our data support that the Hh pathway in DLBCL is aberrantly activated as its activation is in part mediated by external Hh ligands (autocrine and paracrine Hh signaling loops) (5,16) but also intrinsically by cross-talks with other oncogenic pathways (22).…”
supporting
confidence: 72%
“…26 These findings are further supported by the observation that ABCB1 and ABCG2 promoter regions have the consensus sequence of Gli-binding site, and Gli-1 directly bound to the consensus GACCACCCA-like motif located in the promoter regions of ABCB1 and ABCG2 to regulate their transcription in B-cell lymphoma and ovarian cancer cells. 27,28 However, our results demonstrate that ABCC1 was highly expressed in Huh-7-DN and Huh-7-trans cells; in Figure 7 The effects of LDE225 and itraconazole on expression of Gli-1, Gli-2, and ABCC1 in Huh-7-DN subpopulation. Huh-7-DN cells were exposed to LDE225 or itraconazole at various concentrations as indicated for 24 h. mRNA levels of Gli-1, Gli-2, and ABCC1 in Huh-7-DN subpopulation were determined by quantitative RT-PCR, using untreated Huh-7 cells as a control.…”
Section: Discussionmentioning
confidence: 65%
“…We further demonstrated that the canonical Hh ligand-PTCH1-SMO-GLI1 axis plays important roles in cell proliferation, survival, and chemotolerance in this lymphoma subtype. [12][13][14][15][16] Regulators of GLI1's activities include SNF5, a core subunit of the adenosine trisphophate (ATP)-dependent SWItch/Sucrose NonFermentable chromatin remodeling complex, which modulates its transcriptional activities. 17 Hh signaling, meanwhile, promotes the transcriptional activity of both GLI1 and GLI2 proteins by promoting their deacetylation via HDAC1 upregulation.…”
Section: Introductionmentioning
confidence: 99%